Examining public perceptions of President Jokowi's dynastic politics - Jihad, Rajendra Walad; Az’zahra, Dinny Indhikri (Universitas Islam Malang, 2025)
The growing phenomenon of dynastic politics has sparked a debate in the public sphere, especially about the dynastic politics that President Jokowi is building. This research describes the perceptions of the people in Solo and Semarang regarding this phenomenon. The two cities were chosen because they have different levels of emotional closeness to President Jokowi. This research uses quantitative methods with a descriptive approach. The research sample consisted of 100 respondents in each city, selected using a multistage random sampling technique. Data were collected using a questionnaire with a Likert scale to measure people's knowledge, feelings and evaluations. The research results show that people's understanding of dynastic politics is in the high category with a cognitive score rate of 81.38% in Solo and 80.97% in Semarang. The public's feelings and assessment of President Jokowi's dynasty policy is in the middle category with an affective score percentage of 64.39% in Solo and 60.90% in Semarang, as well as an evaluation score percentage of 59.29% in Solo and 52.66% in Semarang. These findings indicate that although the people of Solo City and Semarang City have a good understanding of the politics of President Jokowi's dynasty, they tend to have negative feelings and judgments. It is hoped that this research can contribute to enriching academic discourse and provide recommendations for public policy regarding regulations in minimizing the practice of dynastic politics in Indonesia.